A Dawson type P2W 18 Preparation of CdS photocatalyst

By combining Dawson structure heteropoly acid P2W18 with CdS, P2W18/CdS photocatalyst was prepared, which solved the application limitations of Dawson structure heteropoly acid in photocatalysis, achieved efficient photocatalytic degradation effect, and demonstrated good Recyclability and structural stability.

CN115487828BActive Publication Date: 2025-02-18JILIN INST OF CHEM TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211169198.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-26
Publication Date
2025-02-18
Estimated Expiration
2042-09-26

AI Technical Summary

Technical Problem

The application of Dawson structural heteropolyacids in photocatalysis has limitations, especially in terms of light absorption range and catalytic efficiency.

Method used

By compounding Dawson structural heteropolyacid P2W18 with CdS, a P2W18/CdS photocatalyst was prepared, and its photocatalytic performance was improved through specific preparation steps and conditions.

Benefits of technology

The high-efficiency photocatalytic degradation of Rhodamine B by P2W18/CdS photocatalyst under xenon lamp irradiation was achieved, with a degradation rate of 90.34%, and the degradation rate of 81.1% was maintained after three consecutive cycle experiments, demonstrating good recycling. and structural stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115487828B_ABST
    Figure CN115487828B_ABST
Patent Text Reader

Abstract

The invention discloses a composite material P 2 W 18 The preparation method of CdS photocatalyst is to first synthesize Dawsom type structure heteropoly acid P 2 W 18 and CdS, and then compound the two materials. 2 W 18 The photocatalytic activity of the material was investigated by using CdS to capture free radicals on Rhodamine B. 2 W 18 The optimal conditions for photocatalytic degradation of Rhodamine B by CdS are as follows: the initial Rhodamine B concentration is 30 mg / L, the catalyst P 2 W 18 / CdS accounts for 5wt% of the material. At this time, the pH is 7, the photocatalytic activity of the catalyst is the highest, and the degradation rate can reach 90.34%; and after three consecutive experiments, the degradation rate can reach 81.1%. The catalyst has good recyclability and structural stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photocatalysts, and in particular to a Dawson type P2W 18 / CdS photocatalyst preparation method. Background Art

[0002] As a green technology with important application prospects, photocatalysis has attracted widespread attention because it can effectively repair the environment and convert energy by utilizing photochemical reactions generated by sunlight and photocatalysts. As early as 1967, Fujishima and Honda first discovered the photocatalytic effect, using TiO2 as the working electrode to photocatalytically split water to produce hydrogen and oxygen, and named it the Honda-Fujishima effect. In the photocatalytic process, photocatalysts determine the generation of photogenerated carriers, which directly affects the efficiency of photocatalysis. Therefore, synthesizing photocatalysts with a wide light absorption range, high catalytic efficiency, reusability, and no secondary pollution is an important link in photocatalyst research. Today, a variety of photocatalysts are widely studied, including polyoxometalates, transition metal oxides (sulfides), precious metals, composite nanomaterials, and other types of photocatalysts.

[0003] Heteropolyacids are catalytic materials with excellent performance. Photocatalytic degradation of organic matter has very attractive application prospects. By coupling with other materials such as precious metal nanoparticles or semiconductor materials, the performance and application of heteropolyacids can be greatly improved by modifying or functionalizing the heteropolyacid units. Therefore, designing and constructing polyacid-based photocatalysts with excellent catalytic activity has become an important challenge in the field of heteropolyacid photocatalysis.

[0004] CdS is a semiconductor material that is currently being studied more. It has a wide absorption range for visible light and good light absorption in the range of 520nm, which is not available in Dawson structure heteropoly acids. In addition, the small-sized CdS has a large specific surface area, can fully contact the target pollutants, and provides more active sites, which helps to increase the rate of photocatalytic reactions. If it is compounded with Dawson structure heteropoly acids, the composite catalyst also has better catalytic performance, so that it can be better used in heterogeneous catalytic systems. Therefore, the limitations of Dawson structure heteropoly acids in photocatalysis can be overcome by introducing CdS.

[0005] This patent successfully prepared Dawson structure phosphotungstic heteropoly acid P2W 18 and CdS, and the two materials were composited to successfully prepare the heteropoly acid composite catalyst P2W 18 / CdS, under xenon lamp irradiation, with P2W 18 / CdS was used to carry out photocatalytic test on rhodamine B and the activity of the catalyst was investigated. Summary of the invention

[0006] Based on the technical problems existing in the background technology, the present invention proposes a Dawson type P2W 18 / CdS photocatalyst method.

[0007] The technical solution of the present invention is as follows:

[0008] A method for preparing a magnetically controllable heteropolyacid photocatalyst comprises the following steps:

[0009] Step 1: Preparation of Dawson-type heteropolyacid P2W 18 ;

[0010] Step 2, preparing CdS;

[0011] Step 3: Prepare P2W 18 / CdS.

[0012] Preferably, in step 1, Dawson type heteropoly acid P2W 18 The specific steps of preparation are as follows:

[0013] Sodium tungstate is dissolved in deionized water, orthophosphoric acid is added, the solution is refluxed and heated for 3-6 hours, ammonium chloride is added after cooling, and it is stirred for 5-20 minutes and then centrifuged. The precipitate is dissolved in water and ammonium chloride is added to precipitate again. After stirring for 5-20 minutes, centrifuge and dissolve the precipitate in warm water (30℃-50℃). Filter with filter paper and evaporate the clear solution indoors. After 2 days, potassium chloride is added to the filtrate and the precipitate is dissolved in hot water at 65℃-90℃. When slowly cooled to 10℃-25℃, white needle-like substance (K 14 5W 30 O 110 ·H2O) for 4-8 hours, filter with filter paper. After removing impurities, heat the solution to boiling, cool it, and filter it again. Add potassium chloride to the filtrate, centrifuge it, and put the resulting precipitate into a vacuum drying oven at 30℃-50℃ for drying. Dissolve the powder in warm water (30℃-50℃), acidify it with hydrochloric acid to pH 1-3, evaporate it at room temperature, and collect the yellow crystal heteropoly acid P2W 18 ;

[0014] Preferably, the specific steps of step 2, preparation of CdS are as follows:

[0015] Dissolve cadmium nitrate in ultrapure water, heat to 60℃-85℃ with stirring, and then add freshly prepared sodium sulfide solution to the solution. An orange-yellow solution is immediately obtained. The reaction is maintained at 60℃-85℃ and refluxed for 1-6 hours. The final reaction precipitate is centrifuged and washed with anhydrous ethanol. After repeated twice, it is washed with ultrapure water. The precipitate is placed in a vacuum drying oven and dried at 50℃-80℃ to obtain a sample CdS powder;

[0016] Preferably, the step 3, Dawson type P2W 18 The specific steps for preparing the CdS photocatalyst are as follows:

[0017] Get P2W 18 , dissolved in water, pure CdS was added, and a suspension was formed by stirring. After 10-50 minutes, the prepared hexadecyltrimethylammonium bromide (CTAB) aqueous solution was added to the mixed solution, and the reaction was continued for 20-30 hours. After that, the precipitate was obtained by centrifugation, washed with deionized water and ethanol several times, and the precipitate was separated and placed in an oven to dry to obtain P2W 18 / CdS samples. Among them, CdS and P2W 18 The mass ratio is 1%-15%.

[0018] The invention is beneficial in that: the invention synthesizes Dawson type structure heteropoly acid P2W 18 and CdS, and the two materials were composited to successfully prepare the Dawson type P2W 18 / CdS. Under xenon lamp irradiation, Dawson type P2W 18 / CdS was used to conduct photocatalytic test on Eosin B. Under xenon lamp irradiation, P2W 18 / CdS was used to conduct photocatalytic and free radical capture experiments on rhodamine B, and the photocatalytic activity of the material was investigated. 18 The optimal conditions for photocatalytic degradation of Rhodamine B by CdS are as follows: the initial Rhodamine B concentration is 30 mg / L, the catalyst P2W 18 / CdS accounts for 5wt% in the material. At this time, the pH is 7, the photocatalytic activity of the catalyst is the highest, and the degradation rate can reach 90.34%; and after three consecutive cycle experiments, the degradation rate can reach 81.1%. The catalyst has good recyclability and structural stability.

[0019] The photocatalytic degradation mechanism of the composite material was explored through the results of EIS, CV, PL tests and free radical capture experiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 :Composite material P2W 18 Fourier transform infrared spectrum of / CdS;

[0021] Figure 2 :Composite material P2W 18 / X-ray powder diffraction pattern of CdS;

[0022] Figure 3 :Scanning electron microscopy image (a) P2W 18 (b)CdS(cd)P2W 18 / CdS transmission electron microscope (ef) P2W 18 / CdS;

[0023] Figure 4 :P2W 18 UV-visible spectrum of / CdS;

[0024] Figure 5 :P2W with different ratios 18 / CdS composite material fluorescence spectrum;

[0025] Figure 6 :P2W with different ratios 18 Electrochemical impedance spectroscopy of / CdS composite materials;

[0026] Figure 7 :P2W with different ratios 18 Bode spectrum of / CdS composite materials;

[0027] Figure 8 : Effect of RhB concentration on degradation rate at pH 7;

[0028] Fig. 9 :Composite material P2W 18 Effect of different proportions of / CdS on degradation rate;

[0029] Fig.10 :Composite material P2W 18 Effect of different ratios of / CdS on degradation rate;

[0030] Fig.11 :Effect of pH on composite material P2W 18 / CdS visible light photocatalytic degradation of Rhodamine B;

[0031] Fig.12 :Composite material P2W at pH 7 18 UV-visible spectrum of Rhodamine B photocatalytic degradation by CdS;

[0032] Fig.13 : C / C0 variation with time in composite material cycle test;

[0033] Fig.14 : Infrared comparison of composite material cycle test samples;

[0034] Fig.15 : Masking test of triethanolamine photogenerated holes, isopropanol hydroxyl radicals, and benzoquinone superoxide radicals;

[0035] Fig.16 : Photocatalytic mechanism test data under different pH conditions;

[0036] Fig.17 :Cyclic voltammetry test diagram of CdS;

[0037] Fig.18 :Heteropoly acid P2W 18 Cyclic voltammetry test diagram;

[0038] Fig.19 :Composite material P2W 18 Diagram of the mechanism of photocatalytic degradation of Rhodamine B by CdS. DETAILED DESCRIPTION

[0039] Example 1

[0040] A Dawson-type heteropolyacid P2W 18 / CdS photocatalyst preparation method, comprising the following steps

[0041] Step 1: Dawson-type heteropoly acid P2W 18 Preparation:

[0042] Weigh 20g (0.0608mol) of sodium tungstate sample and dissolve it in 40mL of water in a 250mL round-bottom flask, and add 16.8mL (0.2472mol) of 85% orthophosphoric acid. Heat the solution under reflux for 4 hours. After cooling, add 8g of ammonium chloride, stir for 10min and centrifuge. The precipitate is dissolved in 24mL of water and precipitated again by adding 8g of ammonium chloride. Stir for 10min and centrifuge, and the precipitate is dissolved in 10mL of warm water (45℃). Filter with filter paper and evaporate the clear solution indoors. After 2 days, add 3.2g (0.0432mol) of potassium chloride to the filtrate and dissolve the precipitate in 20mL of hot water (80℃). After slowly cooling to 20℃, a white needle-like substance (K 14 5W 30 O 110 ·H2O) for 4-5 hours, filter with filter paper. After removing impurities, heat the solution to boil

[0043] After cooling, filter again. Add 2g potassium chloride to the filtrate, centrifuge, and dry the obtained precipitate in a vacuum oven at 40°C. Dissolve the powder in 16mL warm water (40°C), acidify to pH=2 with hydrochloric acid, evaporate at room temperature, and collect yellow crystals;

[0044] Step 2: Preparation of CdS:

[0045] Dissolve cadmium nitrate (0.1683 g) in 30 mL of ultrapure water, heat to 70 ° C with stirring, and then add freshly prepared sodium sulfide solution (0.5960 g) in 30 mL of solution. An orange-yellow solution is immediately obtained. The reaction is maintained at 70 ° C and refluxed for 3 hours. The final reaction precipitate is centrifuged and washed with anhydrous ethanol. After repeated twice, it is washed with ultrapure water. The precipitate is placed in a vacuum drying oven and dried at 60 ° C to obtain a sample powder;

[0046] Step 3: Dawson-type P2W 18 Preparation of CdS photocatalyst:

[0047] Get P2W 18 , dissolved in 10 mL of water, pure CdS was added, and a suspension was formed by stirring. After 30 minutes, 10 mL of hexadecyltrimethylammonium bromide (CTAB, 0.1 mol / L) aqueous solution was added to the mixed solution, and the reaction was continued for 24 hours. The precipitate was obtained by centrifugation, and washed with deionized water and ethanol several times. The precipitate was separated and dried in an oven to obtain P2W 18 / CdS samples. Among them, CdS and P2W 18 The mass ratios are 1wt%, 3wt%, 5wt% and 8wt% respectively.

[0048] Example 2

[0049] A Dawson-type heteropolyacid P2W 18 / CdS photocatalyst preparation method, comprising the following steps

[0050] Step 1: Dawson-type heteropoly acid P2W 18 Preparation:

[0051] Weigh 20g (0.0608mol) of sodium tungstate sample and dissolve it in 40mL of water in a 250mL round-bottom flask, and add 16.8mL (0.2472mol) of 85% orthophosphoric acid. Heat the solution under reflux for 3 hours. After cooling, add 8g of ammonium chloride, stir for 5min and centrifuge. The precipitate is dissolved in 24mL of water and precipitated again by adding 8g of ammonium chloride. Stir for 20min and centrifuge, and the precipitate is dissolved in 10mL of warm water (35℃). Filter with filter paper and evaporate the clear solution indoors. After 2 days, add 3.2g (0.0432mol) of potassium chloride to the filtrate and dissolve the precipitate in 20mL of hot water (75℃). After slowly cooling to 15℃, a white needle-like substance (K 14 5W 30 O 110·H2O) for 4-5 hours, filter with filter paper. After removing impurities, heat the solution to boiling, cool it, and filter it again. Add 2g potassium chloride to the filtrate, centrifuge it, and put the resulting precipitate into a vacuum drying oven at 40°C to dry it. Dissolve the powder in 16mL warm water (35°C), acidify it with hydrochloric acid to pH=2, evaporate it at room temperature, and collect the yellow crystals;

[0052] Step 2: Preparation of CdS:

[0053] Dissolve cadmium nitrate (0.1683 g) in 30 mL of ultrapure water, heat to 65 ° C with stirring, and then add freshly prepared sodium sulfide solution (0.5960 g) in 30 mL of solution. An orange-yellow solution is immediately obtained. The reaction is maintained at 65 ° C and refluxed for 4 hours. The final reaction precipitate is centrifuged and washed with anhydrous ethanol. After repeated twice, it is washed with ultrapure water. The precipitate is placed in a vacuum drying oven and dried at 55 ° C to obtain a sample powder;

[0054] Step 3: Dawson-type P2W 18 Preparation of CdS photocatalyst:

[0055] Get P2W 18 , dissolved in 10 mL of water, pure CdS was added, and a suspension was formed by stirring. After 25 min, 10 mL of hexadecyltrimethylammonium bromide (CTAB, 0.1 mol / L) aqueous solution was added to the mixed solution, and the reaction was continued for 26 hours. The precipitate was obtained by centrifugation, washed with deionized water and ethanol several times, and the precipitate was separated and dried in an oven to obtain P2W 18 / CdS samples. Among them, CdS and P2W 18 The mass ratios are 1wt%, 3wt%, 5wt% and 8wt% respectively.

[0056] Example 3

[0057] A Dawson-type heteropolyacid P2W 18 The preparation method of / CdS photocatalyst comprises the following steps: Step 1: Dawson type heteropoly acid P2W 18 Preparation:

[0058] Weigh 20g (0.0608mol) of sodium tungstate sample and dissolve it in 40mL of water in a 250mL round-bottom flask, and add 16.8mL (0.2472mol) of 85% orthophosphoric acid. Heat the solution under reflux for 4 hours. After cooling, add 8g of ammonium chloride, stir for 15min and centrifuge. The precipitate is dissolved in 24mL of water and precipitated again by adding 8g of ammonium chloride. Stir for 15min and centrifuge, and the precipitate is dissolved in 10mL of warm water (50℃). Filter with filter paper and evaporate the clear solution indoors. After 2 days, add 3.2g (0.0432mol) of potassium chloride to the filtrate and dissolve the precipitate in 20mL of hot water (85℃). When slowly cooled to 20℃, a white needle-like substance (K 14 5W 30 O 110 ·H2O) for 5 hours, filter with filter paper. After removing impurities, heat the solution to boiling, cool it, and filter it again. Add 2g of potassium chloride to the filtrate, centrifuge it, and put the resulting precipitate into a vacuum drying oven at 45°C to dry it. Dissolve the powder in 16mL of warm water (40°C), acidify it to pH=2 with hydrochloric acid, evaporate it at room temperature, and collect the yellow crystals;

[0059] Step 2: Preparation of CdS:

[0060] Dissolve cadmium nitrate (0.1683 g) in 30 mL of ultrapure water, heat to 85 °C with stirring, and then add freshly prepared sodium sulfide solution (0.5960 g) to 30 mL of the solution. An orange-yellow solution is immediately obtained. The reaction is maintained at 75 °C and refluxed for 3 hours. The final reaction precipitate is centrifuged and washed with anhydrous ethanol. After repeated two times, it is washed with ultrapure water. The precipitate is placed in a vacuum drying oven and dried at 65 °C to obtain a sample powder;

[0061] Step 3: Dawson-type P2W 18 Preparation of CdS photocatalyst:

[0062] Get P2W 18 , dissolved in 10 mL of water, pure CdS was added, and a suspension was formed by stirring. After 40 minutes, 10 mL of hexadecyltrimethylammonium bromide (CTAB, 0.1 mol / L) aqueous solution was added to the mixed solution, and the reaction was continued for 28 hours. The precipitate was obtained by centrifugation, washed with deionized water and ethanol several times, and the precipitate was separated and dried in an oven to obtain P2W 18 / CdS samples. Among them, CdS and P2W 18 The mass ratios are 1wt%, 3wt%, 5wt% and 8wt% respectively.

[0063] The following is the P2W prepared in Example 1 18 / CdS composite materials were characterized.

[0064] , infrared spectroscopy characterization of composite materials

[0065] P2W was confirmed by FT-IR spectroscopy 18 The structural integrity of the Dawson unit in the / CdS composite material. The Fourier transform infrared spectra of the composite materials with different ingredient ratios are shown in Figure 2. Figure 1 , where CdS and P2W 18 The ratios of the samples were 1wt%, 3wt%, 5wt% and 8wt% respectively. All samples showed a peak at 1092cm -1 , 960cm -1 , 917cm -1 and 780cm -1 Four characteristic absorption peaks appear at the P2W, which can be attributed to the saturated Dawson structure. 18 The stretching vibrations of the samples are PO, W=O, W-Ob-W and W-Oc-W. Since CTAB was added during the sample-compounding process, the characteristic peaks of CTAB can be observed in the infrared spectrum, which are 2923cm -1 , 2852cm -1 , 1465cm -1 and 1373cm -1 .

[0066] , X-ray powder diffraction characterization of composite materials

[0067] P2W was characterized by X-ray diffraction (XRD) test. 18 、P2W 18 -CTAB and composite photocatalyst P2W 18 The crystal structure and chemical composition of CdS / CdS (with different CdS loading) nanoparticles, such as Figure 2 By P2W 18 and P2W 18 -CTAB XRD patterns, it was found that after adding surfactant CTAB, P2W 18 -CTAB diffraction peaks have changed significantly, which is because the surfactant changes the growth direction of the crystal surface. 18 / CdS and P2W18-CTAB XRD patterns, it is found that the diffraction peaks of the XRD pattern of the composite material after loading CdS have no obvious changes, but the peak intensity changes slightly, which indicates that the loading of CdS does not affect the crystal structure of P2W18. It can be seen from the figure that the XRD diffraction peaks of the composite materials P2W18 / CdS with different ingredient ratios have the same position and peak shape, but P2W 18 No diffraction peak of CdS was observed in the XRD pattern of / CdS, which may be due to the low CdS loading amount.

[0068] , Electron Microscope Testing of Composite Materials

[0069] To observe pure P2W 18 , CdS and P2W 18 The particle size and surface morphology of the CdS / CdS composite materials were tested by SEM. Figure 3 (a) P2W 18 Scanning electron microscope test image, P2W 18 Irregular shape. Figure 3 (b) It can be seen that the synthesized cadmium sulfide is relatively uniform, with an average size of about 50nm. Figure 3 (cd) and (ef) are P2W 18 The scanning electron microscope and transmission electron microscope images of the P2W / CdS composite material clearly show that the heteropoly acid changes from an irregular shape to a block distribution under the influence of the surfactant CTAB. This is because the surfactant can dynamically control the growth process of the crystal, affecting its growth rate and the growth direction of the crystal surface, which causes the morphology of the heteropoly acid to change. We can observe that P2W 18 The CdS nanoparticles are tightly adhered to each other and CdS is well dispersed on the heteropolyacid, which indicates that P2W 18 / CdS heterojunction has been successfully prepared. Cadmium sulfide nanoparticles are small in size and large in specific surface area, which is conducive to full contact with pollutants during catalytic reactions and can provide more active sites. 18 By constructing a heterojunction structure with CdS nanoparticles, a close interfacial contact is formed, which is conducive to rapid electron transfer, thereby improving the photocatalytic efficiency.

[0070] , UV-Vis spectroscopy characterization of composite materials

[0071] Figure 4 Pure P2W 18 , CdS and composite materials (P2W with different CdS loadings 18 / CdS) UV-visible absorption spectrum, the test range is 200-800nm. As shown in the figure, P2W 18 The absorption edge of the / CdS composite material gradually increases and extends to longer wavelengths. It can be seen that the characteristic absorption peaks at around 360nm and 500nm are consistent with the peak positions of pure heteropoly acid and CdS, which also proves that P2W 18 / CdS composite successfully. At the same time, with P2W 18 Compared with the absorption spectrum of the composite catalyst P2W 18 / CdS constructs a heterojunction with a low energy gap, and the absorption edge moves significantly to the long-wave direction, that is, it red-shifts, expanding the light absorption range. It shows strong absorption in the visible light region, which can improve the utilization rate of sunlight and help improve photocatalytic activity. According to the UV-visible absorption spectrum, as the CdS ratio increases, the composite catalyst P2W 18 The visible light absorption of / CdS in the range of 400-550nm gradually increases, and the absorption edges can be extended to 542nm, 553nm, 577nm and 593nm respectively.

[0072] , fluorescence spectroscopy characterization of composite materials

[0073] Through fluorescence spectroscopy analysis, the recombination rate and transfer efficiency of photogenerated electron-hole pairs in the prepared catalyst were investigated, which is considered to be the main key factor in improving photocatalytic performance. After the catalyst is irradiated with light, it is excited to produce electron-hole pairs, and the electrons jump from the valence band to the conduction band, generating an equal number of holes in the conduction band. Only when the electron holes recombine again and are released in the form of light will the luminescence phenomenon occur. The higher the fluorescence intensity, the easier it is for the electron-hole pairs of the material to recombine, and the lower the photocatalytic activity. Under the excitation light of 403nm, P2W was obtained. 18 / CdS composite materials, such as Figure 5 As shown. All samples showed similar fluorescence emission peaks at 604nm. The fluorescence intensities of composite materials with different ratios are different, so the separation degree and transfer effect of photogenerated electron-hole pairs are also different. Compared with the composite materials with ratios of 1wt%, 3wt%, and 8wt%, the composite material with a CdS ratio of 5wt% has a lower fluorescence peak intensity, indicating that the composite material with a CdS ratio of 5wt% has the lowest carrier recombination rate and higher photocatalytic activity.

[0074] , Electrochemical impedance spectroscopy of composite materials

[0075] Electrochemical impedance spectroscopy (EIS) can also be used to investigate the separation efficiency of photogenerated charge carriers in the prepared catalyst. Therefore, we conducted EIS tests on the samples. Figure 6 The Nyquist plots of electrodes containing composite materials with CdS ratios of 1wt%, 3wt%, 5wt%, and 8wt% respectively. It is generally believed that the arc radius of the Nyquist plot is positively correlated with the charge transfer impedance (Rct) of the sample. The smaller the arc radius, the smaller the charge transfer impedance. As can be seen from the figure, when the CdS ratio is different, the composite material P2W 18 The arc radius of the composite material P2W with a CdS ratio of 5wt% is different, and the order is 5wt%>8wt%>3wt%>1wt%. 18 / CdS has the smallest arc radius and the smallest charge transfer impedance. At the same time, after fitting, when the CdS ratio is 5wt%, the impedance data inflection point is the smallest, which is 351.1Ω, indicating that the photogenerated carrier separation efficiency is high and the efficient transfer at the electrode / electrolyte interface is conducive to the photocatalytic reaction. The AC impedance spectrum shows that the composite material with a ratio of 5wt% CdS has a lower charge transfer resistance than the composite materials with a ratio of 1wt%, 3wt%, and 8wt% CdS (impedances are 417.4Ω, 355.2Ω, and 450.1Ω, respectively).

[0076] The lower the cross-value in the Bode diagram, the faster the photogenerated carriers are generated. Figure 7 It can be judged that CdS and P2W 18 When the proportion is 5wt%, the composite material P2W 18 / CdS produces electron-hole pairs most rapidly, which is beneficial to the photocatalytic reaction and has the highest theoretical photocatalytic activity.

[0077] 、Composite material P2W 18 / CdS photocatalytic performance test

[0078] P2W 18 / CdS nanocomposite materials were used as photocatalysts to simulate sunlight and conduct photocatalytic degradation experiments on Rhodamine B solution. The effects of different experimental factors (Rhodamine B solution concentration, catalyst ratio, and solution pH) on photocatalytic degradation were systematically analyzed. Photocatalytic experiments were conducted in 0.1g of photocatalyst and solutions of a certain concentration to evaluate the P2W 18 The photocatalytic activity of the composite photocatalyst was evaluated by studying the cycle performance of degradation of Rhodamine B.

[0079] By adding triethanolamine (h + quencher), isopropanol (·OH scavenger) and p-benzoquinone (·O2 - quencher), combined with photocatalytic data, to explore P2W 18 The main active species in the photocatalytic degradation of Rhodamine B by CdS / CdS composites.

[0080] , Effect of different initial concentrations on photocatalysis

[0081] The effect of the concentration of Rhodamine B on the photocatalytic reaction rate was evaluated by changing the initial concentration of Rhodamine B (30 mg / L, 40 mg / L and 50 mg / L). Figure 8 As shown. Figure 8It can be seen that by gradually increasing the initial concentration of Rhodamine B, the photocatalytic degradation rate of Rhodamine B can be observed to gradually decrease. The overall effect of dark light adsorption and photocatalysis of Rhodamine B solution at 50 mg / L is not very good, with adsorption of about 42%, photolysis of 37%, and the final treatment volume of Rhodamine B solution of about 79%. When the concentration of Rhodamine B is 40 mg / L, the final treatment volume is about 88%. And because of the lower concentration, the photocatalytic efficiency of Rhodamine B at a concentration of 30 mg / L is the highest, reaching 92%, which is 13% higher than the photocatalytic efficiency of 50 mg / L. As the initial concentration of Rhodamine B increases, it takes a longer time to achieve the complete reduction of Rhodamine B. According to P2W 18 The first-order kinetics fitting diagram of photocatalytic degradation of Rhodamine B by / CdS ( Fig. 9 ), when the concentration of rhodamine B is 30 mg / L, P2W 18 / CdS composite material still has the best photocatalytic degradation activity (k = 0.0188min-1), which is consistent with the degradation result of rhodamine B.

[0082] , Effect of different ingredient ratios on photocatalysis

[0083] At a rhodamine B concentration of 30 mg / L and pH 7, different ratios of CdS and P2W were studied. 18 The effects of catalysts with different proportions (1wt%, 3wt%, 5wt%, and 8wt%) on the photocatalytic degradation of Rhodamine B are shown in the following table. Fig.10 shown. Fig.10 The figure shows the P2W under simulated sunlight. 18 The time-varying curve of the degradation of Rhodamine B by using CdS as a photocatalyst. It can be seen that under the same conditions of controlling the concentration of Rhodamine B to 30 mg / L and the amount of catalyst added to 0.1 g, the composite material P2W 18 / CdS has better photocatalytic effect than pure P2W 18 The composite material with a CdS ratio of 5% has the best photocatalytic degradation effect on rhodamine B, while the ratio is 1wt%, 3wt% and 8wt%, which slightly decreases, indicating that the ratio of CdS of 5wt% is the optimal degradation point, which can reach about 92%. When the ratio is 1wt%, 3wt% and 8wt%, the final photocatalytic degradation rate can reach 82%, 85% and 89% respectively. Fig.11 It is a composite material P2W with different ingredient ratios 18 The first-order kinetic fitting diagram of the photocatalytic degradation of Rhodamine B by / CdS shows the photocatalytic activity of different composite catalysts. It can be seen from the figure that with the increase of CdS loading, CdS and P2W 18 When the proportion of ingredients is 5%, the degradation rate of rhodamine B is the highest, and k is 0.0188min -1, which is better than other photocatalysts with different ratios, which may be due to the fact that the increased cadmium sulfide loading provides more active sites for the reaction. 18 When the ratio reaches 8wt%, the degree of CdS agglomeration gradually increases, and the contact area with heteropolyacid decreases slightly, resulting in a larger resistance to electron transfer and a decrease in photocatalytic activity.

[0084] , Effect of different pH values ​​on photocatalysis

[0085] Under the condition that the concentration of rhodamine B solution is 30mg / L, a composite material with a CdS ratio of 5wt% was selected to carry out photocatalytic experiments to study the effect of different pH values ​​on the photocatalytic activity of P2W. 18 The effect of / CdS on the photocatalytic degradation of Rhodamine B. Fig.12 As shown. Fig.12 It can be seen that the photocatalytic degradation efficiency of Rhodamine B is different at different pH values. When the pH is equal to 7, the photocatalytic ability is better, and the final degradation rate can reach 92%. As the pH gradually decreases, the photocatalytic effect generally shows a trend of decreasing and then increasing. When the pH is equal to 3, 4, 5, and 6, the final degradation rates of Rhodamine B are 79%, 76%, 86%, and 85%, respectively. At pH 1 and 2, the photocatalytic effect reaches another peak, and the final photocatalytic results are all 92%. This may be due to changes in the photocatalytic mechanism, so there are two peaks in the photocatalytic effect. However, due to too low a pH value, the catalyst will be corroded by acid, and the catalyst will have a shortened life. Therefore, when the photocatalytic degradation effect is almost the same, this experiment selects pH 7 as the optimal pH for photocatalytic degradation of Rhodamine B.

[0086] 7.4. Photocatalytic cycle experiment of composite materials

[0087] The ideal photocatalytic performance of photocatalysts plays an extremely important role in practical applications. Similarly, their stability also plays an equally important role. 18 / CdS is used as the catalyst, and three consecutive cycle experiments of degrading rhodamine B are carried out to determine whether the photocatalyst is stable and reusable. Fig.13 It shows that after three cycles of experiments, P2W 18 The photocatalytic activity of P2W / CdS decreased slightly from 87.2% to 82.4% in the first cycle and finally to 81.1% in the third cycle, which may be related to the sample loss during the cycle. 18 / CdS has sufficiently stable photocatalytic degradation activity. Fig.14 This is the infrared comparison picture of the composite material cycle test sample. Fig.14 Know, P2W before and after the cycle experiment 18The structure of the / CdS photocatalyst remains unchanged, and the complete Dawson structure is still maintained, with little activity loss, which further confirms that the P2W 18 / CdS has good stability.

[0088] , Photocatalytic mechanism test

[0089] 8.1 Free Radical Capture Experiment

[0090] To study P2W 18 We conducted free radical and hole capture experiments to identify the main reactive species in the degradation of Rhodamine B by CdS / CdS. By adding triethanolamine, isopropanol and p-benzoquinone to the photocatalytic reaction system as capture agents for photogenerated holes, hydroxyl radicals and superoxide radicals, respectively, the main reactive species were determined based on their inhibition degree on the photocatalytic degradation rate of Rhodamine B. Fig.15 When triethanolamine or benzoquinone was added, the photogenerated holes or superoxide radicals were masked, and the photocatalytic effect of the composite material was reduced, proving that photogenerated holes and superoxide radicals were the limiting factors for the photocatalytic decomposition of rhodamine B. Under isopropanol conditions, the photocatalytic degradation rate remained unchanged, and the final catalytic result remained almost unchanged, proving that the hydroxyl radicals masked by isopropanol were not the main factor limiting the photocatalytic activity. This shows that in P2W 18 In the photocatalytic degradation of Rhodamine B by CdS / CdS, photogenerated holes and superoxide radicals are the main active species.

[0091] At different pH values, triethanolamine, isopropanol and p-benzoquinone were added to the photocatalytic system, and the photocatalytic effects were as follows: Fig.16 As shown in the figure. It can be seen from the figure that the photocatalytic mechanism of the composite material is different under different pH conditions. When the pH is 1 and 3, the masking agents triethanolamine, isopropanol and p-benzoquinone are added to the reaction system respectively, and the photocatalytic effect is inhibited, which shows that the photogenerated holes, hydroxyl radicals and superoxide radicals are the main active species of the photocatalytic reaction. Under the conditions of pH 5 and 7, when the masking agents triethanolamine and p-benzoquinone are added respectively, the photocatalytic effect is inhibited, but the addition of isopropanol has no effect on the photocatalytic effect, which shows that the hydroxyl radicals have lost their effect, and only the photogenerated holes and superoxide radicals are the main active substances of photocatalysis. In summary, in the whole process of photocatalysis, under the condition of lower pH value, the mechanism of photocatalysis is the joint action of photogenerated holes, hydroxyl radicals and superoxide radicals, and when the pH is greater than or equal to 5, the photocatalytic mechanism changes, and the active species of photocatalysis are converted into photogenerated holes and superoxide radicals.

[0092] , Photocatalytic mechanism diagram

[0093] Fig.17 and 18 CdS and heteropoly acid P2W18 Cyclic voltammetry test. The electrochemical cyclic voltammetry and UV-visible spectroscopy tests can be used to obtain the CdS and P2W 18 LUMO and Eg values.

[0094] The first reduction potential can be found by cyclic voltammetry curve, and the conduction band energy level and P2W of CdS can be estimated. 18 Through the above two experiments, it can be determined that the conduction band position of CdS is -0.29V ( Fig.17 ),from Fig.18 It can be seen that the LUMO position of polyoxometalates is 0.67 V, which is similar to the LUMO of conventional polyoxometalates. 18 The band gap widths of heteropolyacid P2W are 2.15eV and 2.8eV respectively. 18 HOMO and CdS valence band position (E (HOMO) =E (LUMO) +Eg,E (VB) =E (CB) +Eg), the photocatalytic mechanism diagram of the composite material can be obtained, such as Fig.19 As shown in the figure, the generation of photogenerated electrons, holes and superoxide radicals is described, and the CdS nanomaterials and P2W 18 The electron transfer between them and their energy level matching diagram.

[0095] Based on the above evidence, we deduced and proposed a photocatalytic mechanism. Under light radiation, both heteropolyacid and CdS generate electron-hole pairs. After the heteropolyacid absorbs energy, an energy level transition occurs, from the HOMO energy level to the LUMO energy level, and the photogenerated electrons and photogenerated holes separate and migrate to the surface of the heteropolyacid. After the photogenerated electrons generated in the heteropolyacid transition to the LUMO, they are transferred to the valence band of CdS, where they recombine with the photogenerated holes generated by CdS to cause quenching, consuming the holes of CdS, so that the photogenerated electrons generated by CdS will not be quenched due to re-crossing the band gap. At the same time, it indirectly increases the distance between the conduction band and the valence band of the composite material, inhibits the recombination of electrons and holes, and promotes the photocatalytic reaction. The electrons e- react with the O2 molecules in the aqueous solution to reduce them to ·O2 - , the hole JH2O reacts to produce ·OH, h + , ·OH and ·O2 - They all have strong oxidizing ability, causing organic pollutants to lose electrons and be oxidized.

[0096] , Summary of characterization results

[0097] The present invention successfully synthesized Dawson structure heteropoly acid P2W 18 and CdS, and the two materials were composited to successfully prepare the heteropoly acid composite catalyst P2W18 / CdS, and the catalyst P2W was proved by FT-IR, XRD, UV-vis and SEM characterization methods. 18 / CdS composite was successfully composited. At the same time, under the conditions of simulated sunlight (xenon lamp irradiation), the degradation test of Rhodamine B was carried out using the composite material as a photocatalyst to investigate the photocatalytic activity of the material and determine the P2W 18 The optimal conditions for photocatalytic degradation of Rhodamine B by CdS / P2W are as follows: the initial Rhodamine B concentration is 30 mg / L and the catalyst is CdS / P2W 18 The ratio of ingredients is 5wt% and the pH is 7. At this time, the photocatalytic activity is the highest and the degradation rate can reach 92%. 18 / CdS can still maintain a high catalytic activity after three cycles, and the degradation rate can still reach 81.1%.

[0098] The results of EIS, CV, PL tests and free radical capture experiments were used to explore the Dawson structure heteropolyacid P2W 18 Based on the experimental results, we derived and proposed the photocatalytic mechanism, namely, P2W 18 / CdS is the main active substance for the photocatalytic degradation of Rhodamine B. This provides some new ideas for the construction of highly active heterogeneous heteropolyacid composite photocatalysts in the future.

[0099] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A Dawson-type P2W 18 A method for preparing a CdS photocatalyst, characterized in that: The following steps are involved: Step 1: Preparation of Dawson-type heteropolyacid P2W 18 ; Step 2, preparing CdS; Step 3: Prepare P2W 18 / CdS; Step 1: Dawson type heteropoly acid P2W 18 The specific steps of preparation are as follows: Sodium tungstate is dissolved in deionized water, orthophosphoric acid is added, the solution is refluxed and heated for 3-6 hours, ammonium chloride is added after cooling, stirring for 5min-20min and centrifuging, the precipitate is dissolved in water, ammonium chloride is added to precipitate again, stirring for 5min-20min and centrifuging, the precipitate is dissolved in 30℃-50℃ warm water, filtered with filter paper, the clarified solution is evaporated indoors, after 2 days, potassium chloride is added to the filtrate, the precipitate is dissolved in 65℃-90℃ hot water, and then slowly cooled to 10℃-25℃, white needle-like substance K appears 14 5W 30 O 110 ·H2O After 4-8 hours, filter with filter paper to remove impurities, heat the solution to boiling and then cool, filter again, add potassium chloride to the filtrate, centrifuge, put the obtained precipitate into a vacuum drying oven at 30℃-50℃ for drying, dissolve the powder in 30℃-50℃ warm water, acidify with hydrochloric acid to pH 1-3, evaporate at room temperature, and collect the yellow crystal heteropoly acid P2W 18 ; The specific steps of step 2, preparation of CdS are as follows: Dissolve cadmium nitrate in ultrapure water, heat to 60°C-85°C while stirring, then add freshly prepared sodium sulfide solution into the solution, immediately obtain an orange-yellow solution, keep the reaction at 60°C-85°C, and continue to reflux for 1-6 hours. Finally, centrifuge the reaction precipitate, wash the precipitate with anhydrous ethanol, repeat twice, wash with ultrapure water, and dry the precipitate in a vacuum drying oven at 50°C-80°C to obtain a sample CdS powder; Step 3: P2W 18 The specific steps for preparing / CdS are as follows: Get P2W 18 , dissolved in water, pure CdS was added, and a suspension was formed by stirring. After 10-50 minutes, the prepared hexadecyltrimethylammonium bromide aqueous solution was added to the mixed solution. After the reaction was continued for 20-30 hours, the precipitate was obtained by centrifugation, and washed with deionized water and ethanol for many times. The precipitate was separated and dried in an oven to obtain P2W 18 / CdS samples, where CdS and P2W 18 The mass ratio is 1%-15%.

2. Dawson type P2W as claimed in claim 1 18 A method for preparing a CdS photocatalyst, characterized in that: The following steps are involved: Step 1: Dawson-type heteropoly acid P2W 18 preparation: Weigh 20g, 0.0608mol of sodium tungstate sample and dissolve it in 40mL of water in a 250mL round-bottom flask, add 16.8mL, 0.2472mol of 85% orthophosphoric acid, reflux and heat the solution for 4 hours, add 8g of ammonium chloride after cooling, stir for 10min and centrifuge, dissolve the precipitate in 24mL of water, add 8g of ammonium chloride to precipitate again, stir for 10min and centrifuge, dissolve the precipitate in 10mL of 45℃ warm water, filter with filter paper, evaporate the clear solution indoors, add 3.2g, 0.0432mol of potassium chloride to the filtrate after 2 days, dissolve the precipitate in 20mL of 80℃ hot water, and then slowly cool to 20℃, white needle-like substance K appears. 14 5W 30 O 110 ·H2O After 4-5 hours, filter with filter paper to remove impurities, heat the solution to boiling, cool it, filter it again, add 2g potassium chloride to the filtrate, centrifuge it, put the obtained precipitate into a vacuum drying oven at 40℃ and dry it, dissolve the powder in 16mL 40℃ warm water, acidify it to pH=2 with hydrochloric acid, evaporate it at room temperature, and collect the yellow crystals; Step 2, preparation of CdS: Dissolve 0.1683 g of cadmium nitrate in 30 mL of ultrapure water, heat to 70°C under stirring, then add 0.5960 g of freshly prepared sodium sulfide solution in 30 mL of solution, and immediately obtain an orange-yellow solution. The reaction is maintained at 70°C and refluxed for 3 hours. Finally, the reaction precipitate is centrifuged, and the precipitate is washed with anhydrous ethanol. After repeating twice, it is washed with ultrapure water, and the precipitate is placed in a vacuum drying oven and dried at 60°C to obtain a sample powder; Step 3: Dawson-type P2W 18 Preparation of CdS photocatalyst: Get P2W 18 , dissolved in 10mL water, pure CdS was added, and a suspension was formed by stirring. After 30min, 10mL of 0.1mol / L aqueous solution of hexadecyltrimethylammonium bromide CTAB was added to the mixed solution. After the reaction was continued for 24 hours, the precipitate was obtained by centrifugation, washed with deionized water and ethanol several times, and the precipitate was separated and dried in an oven to obtain P2W. 18 / CdS samples, where CdS and P2W 18 The mass ratios are 1wt%, 3wt%, 5wt% and 8wt% respectively.

Citation Information

Patent Citations

  • Novel Dawson polyacid intercalation hydrotalcite composite material and method of preparing the same

    CN101549288A

  • Preparation method and application of multi-metal oxygen cluster functionalized cadmium sulfide nanowire sensor array

    CN108760629A